Investigations of the throwing biomechanics index in collegiate baseball pitchers - Stokes, H.; Eaton, K.; Zheng, N. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
In the field of sports biomechanics the aim is to improve performance and reduce injury. In this study we create a novel throwing biomechanics index by using logistic regression to identify the most important and significant variables that influence injury. Fifteen biomechanics (kinematic and kinetic) variables were identified using logistic regression and the standards of the throwing biomechanics index were determined based on the healthy and high performing group (ball speed > 80 mph). Z-scores were used to determine the index value for each pitcher. Division 1 and 2 collegiate baseball pitchers participated in this study that were grouped based on their injuries before and after the study compared to the healthy group. The healthy group had the highest throwing biomechanics index and further analysis will provide more insights on both injury and performance. The throwing biomechanics index found significant relationships with the pitcher`s height (p=.0165), mass (p=.0003), age (p =.0099), forearm length (p=.0001), internal flexibility (p=.0015), external ROM (p=.0002), and external flexibility (p=.0142). There is great value in quantifying a throwing biomechanics index for both understanding the injury mechanisms and for improved performance.